Kształtowanie gotowości do zmiany jako element działań preparacyjnych w procesie resocjalizacji - Chojecka, Jana (Wydawnictwo Naukowe UAM, 2016)
This article approximates the main issues relate to question what can make social rehabilitation more effective and efficient. Contemporary research focus on concept of readiness and motivation as main components of effective programming for offenders. In the literature we can find many different definitions used by researchers to describe the fenomenon of being ready, willing and able to engage in social rehabilitation process and to change offending behaviors. I will try to show some theories how people change and some methods which can increase readiness to engage in programms.
Readiness to Change Formation as a Component of Preparation in Social Rehabilitation Process
Keywords: readiness to change; motivation; pretreatment interventions; social rehabilitation for offenders